The standard model of talent development and its discontents - Bailey, R.; Collins, D. (Kinesiology Review, 2013)
Despite evident differences between approaches to talent development, many share a set of common characteristics and presumptions. We call this the Standard Model of Talent Development (SMTD). This model is articulated and the relevant literature drawn out to highlight the model's strengths and weaknesses. The SMTD has been enormously influential, in terms of both policy documentation and practice, and it retains an obvious common sense appeal. However, we will argue that not only is its attractiveness illusionary and inconsistent to the emerging evidence base from research, but it is also undesirable from a variety of perspectives and desired outcomes. In short, we suggest that the most common system for identifying talent is unsubstantiated from both a process and an outcome perspective.